KONSISTENSI METODE SHARPE, TREYNOR, DAN JENSEN&rsquo - , Andrew Argado Kirana S ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Investment is temporarily postponed consumption for greater future consumption. Two elements that investment are return and risk. One of the investment instrument is protected funds. Amid the uncertainty of global financial conditions, which resulted in price declines in stocks, bonds and other financial instruments, protected funds are expected to protect their initial investment while still providing returns to investors. Evaluating the performance of mutual funds generally have 2 approaches, namely measuring the level of mutual fund returns and measures the level of risk-adjusted performance. Using risk-adjusted performance, there are three methods commonly used by investment managers. Yhe methods are Sharpe, Treynor and Jensen Performance Index. This study examines whether there is consistency in measurement methods Sharpe, Treynor and Jensen performance of protected funds in the period from January 2007 until December 2009. From the results of calculations using the statistical test of Kendall's W Test, can be seen that asympt.sig value is 0.319. Thus concluded there was no consistency in protected mutual fund performance evaluation period January 2007 to December 2009 using Sharpe index, Treynor index and Jensen's Alpha index.